Modes of delivery and indications in women with COVID-19: a regional observational study in Japan - Shoichi Magawa; Shintaro Maki; Yuya Tamaishi; Naosuke Enomoto; Sho Takakura; Masafumi Nii; Kyohei Yamaguchi; Toru Hirata; Kenji Nagao; Yuka Maegawa; Kazuhiro Osato; Hiroaki Tanaka; et al. (Journal of Obstetrics and Gynaecology)
Background During the coronavirus disease (COVID-19) pandemic, caesarean section (CS) has been the preferred deliver method for pregnant women with COVID-19 in order to limit the use of hospital beds and prevent morbidity among healthcare workers.Methods To evaluate delivery methods used during the COVID-19 pandemic as well as the rates of adverse events and healthcare worker morbidity associated with caesarean deliveries.Methods We investigated maternal and neonatal backgrounds, delivery methods, indications and complication rates among pregnant women with COVID-19 from December 2020 to August 2022 in Mie Prefecture, Japan. The predominant mutation period was classified as the pre-Delta, Delta and Omicron epoch.Results Of the 1291 pregnant women with COVID-19, 59 delivered; 23 had a vaginal delivery and 36 underwent CS. Thirteen underwent CS with no medical indications other than mild COVID-19, all during the Omicron epoch. Neonatal complications occurred significantly more often in CS than in vaginal delivery. COVID-19 in healthcare workers was not attributable to the delivery process.Conclusion The number of CS with no medical indications and neonatal complications related to CS increased during the COVID-19 pandemic. Although this study included centres that performed vaginal deliveries during COVID-19, there were no cases of COVID-19 in healthcare workers. It is possible that the number of CS and neonatal complications could have been reduced by establishing a system for vaginal delivery in pregnant women with recent-onset COVID-19, given that there were no cases of COVID-19 among the healthcare workers included in the study.